Do payroll tax cuts boost formal jobs in developing countries? - Carmen Pagés (IZA World of Labor, 2017)
Informal employment accounts for more than half of total employment in Latin America and the Caribbean, and an even higher percentage in Africa and South Asia. It is associated with lack of social insurance, low tax collection, and low productivity jobs. Lowering payroll taxes is a potential lever to increase formal employment and extend social insurance coverage among the labor force. However, the effects of tax cuts vary across countries, often resulting in large wage shifts but relatively small employment effects. Cutting payroll taxes requires levying other taxes to compensate for lost revenue, which may be difficult in developing economies.
Keywords: H20; J46; O17; 330; payroll taxes; formal employment; wage shifts; developing countries